Edukasi Hukum Tentang Hak Reproduksi Wanita Dalam Perspektif Hukum Positif Di Indonesia - Bawon Nul Hakim; Wahida Yuliana (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Women’s reproductive rights constitute an integral part of human rights guaranteed by the constitution and statutory regulations in Indonesia. Although the positive legal framework has comprehensively regulated the protection of reproductive health rights, a significant gap remains between legal norms and their implementation at the community level. This gap is reflected in limited legal awareness, persistent social stigma, and unequal access to reproductive health services. This community service program aims to enhance public legal awareness and understanding of women’s reproductive rights from the perspective of Indonesian positive law. The activity employed legal education methods through structured lectures, interactive discussions, and case-based reflections, referring primarily to Law Number 17 of 2023 on Health and Law Number 23 of 2004 on the Elimination of Domestic Violence. The results indicate an improvement in participants’ understanding of preventive and repressive legal protection, the right to access reproductive health services, and the obligations of the state and society in ensuring the fulfillment of these rights. Furthermore, the program highlights the strategic role of legal education in bridging the gap between normative legal provisions and social practice. Therefore, this community service activity contributes to strengthening legal awareness and promoting fair, human rights-based, and sustainable protection of women’s reproductive rights in Indonesia.